Analysing urban government at a distance: with and beyond actor-network theory - Söderström, Ola (London: Palgrave MacMillan, 2017)
This Chapter aims to identify the reach and limits of concepts developed within actor-network theory (ANT) for understanding contemporary transformations in urban planning and development. It focuses on the analysis of urban government at a distance through the role of three important mediators: models, images and discourses. I argue that ANT's focus on intermediaries and translation procedures in the construction of translocal planning assemblages is heuristically powerful. However, to better understand the relatedness of urban policies, urban and planning studies need to look beyond these classic ANT tools. In particular, we need a broader reception of ANT as well as the resources of other approaches to capture the role of global urban policymaking, computer-generated images and post-coloniality.